The Characterization of The Main Characte and Ivan Ilyich Character Analysis in The Short Stories The Death of Ivan Ilyich Written By Leo Tolystoy - Gilang Bintang; Satria Raditiyanto (Equivalent: Jurnal Ilmiah Sosial Teknik, 2023)
In this Literature research, the researcher will analyze about the characterization from the several main character and Ivan Ilyich character analysis as the main character from the short stories: The Death of Ivan Ilyich Written by Leo Tolystoy. This short stories also has scores another triumph for Nobel Prize winner. This Short stories is the filled with Ivan Ilyich profound vision of life, as the honest Judgment of a high court prosecutor in 19th-century Russian miserable husband, the proud father, and upwardly-mobile member of Russia's professional class, the object of Tolstoy's unremitting satire. The researcher will completed the character explanation with the description about the several characterizations from the another main character base from the short story written by Leo Tolystoy. Short stories are short stories with a small page 20 until 50 pages, considerably longer, depicting a real life in a complex sequence of events. Rees states that short stories is the most widely being read of all kinds of literature (1973:106). The Literature research will analyze about the characterization from the several main character, and analyze the Ivan Ilyich character base from E.M. Foster (1927), and the Ivan Ilyich obsession base from the short stories with using the structural elements of literature study.